Pretreatment of MQA, a caffeoylquinic acid derivative compound, protects against H2O2-induced oxidative stress in SH-SY5Y cells. (1st December 2016) - Tian, Xing; Gao, Lingyue; An, Li; Jiang, Xiaowen; Bai, Junpeng; Huang, Jian; Meng, Weihong; Zhao, Qingchun
Abstract : Objectives : Compound MQA (1, 5-O-dicaffeoyl-3-O-[4-malic acid methyl ester]-quinic acid) is a natural caffeoylquinic acid derivative isolated from Arctium lappa L. roots. This study aims to explore the neuroprotective effects of MQA against hydrogen peroxide (H2 O2 )-induced oxidative stress in SH-SY5Y neuroblastoma cells. Methods: The SH-SY5Y cells were divided into four groups, including control, 20 μM MQA, 200 μM H2O2, 200 μM H2O2 + 20 μM MQA groups. The effects of MQA on H2 O2 -induced cell death were measured by MTT and LDH assays. Hoechst 33342 and Annexin V-PI double staining were used to observed H2O2-induced apoptosis. Also, the effects of MQA on antioxidant system and mitochondrial pathway were explored. Further, steady-state phosphorylation levels of ERK1/2, Akt and GSK-3β were examined by Western blot analysis. Results: Pretreatment with MQA prevented cell death in SH-SY5Y cells exposed to 200 μM H2O2 for 3 h. Meanwhile, Hoechst 33342 and Annexin V-PI double staining showed that MQA attenuated H2 O2 -induced apoptosis. These changes are related to elevation in SOD activity, reduction in MDA production and ROS formation, and increases in mitochondrial membrane potential (MMP). In addition, the potential mechanisms of MQA against H2 O2 -induced apoptosis are associated with increases in the Bcl-2/Bax ratio, decreases in cytochrome c release, caspase-3 and caspase-9 expressions, phosphorylation of ERK1/2, and dephosphorylation of AKT and GSK-3β. Conclusion: These findings suggest that protective effects of MQA against H2 O2 -induced apoptosis might be associated with mitochondrial apoptosis, ERK1/2 and AKT/GSK-3β pathway.